2019
DOI: 10.1002/cyto.a.23906
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning of Discriminative Gate Locations for Clinical Diagnosis

Abstract: High‐throughput single‐cell cytometry technologies have significantly improved our understanding of cellular phenotypes to support translational research and the clinical diagnosis of hematological and immunological diseases. However, subjective and ad hoc manual gating analysis does not adequately handle the increasing volume and heterogeneity of cytometry data for optimal diagnosis. Prior work has shown that machine learning can be applied to classify cytometry samples effectively. However, many of the machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Recent studies explored the use of AI in other areas of flow cytometric analysis beyond disease classification. Studies indicated that an AI-based method for automated gating of cell populations in flow cytometry data achieves high accuracy and consistency across different datasets [ 68 ]. In addition, Arvaniti and colleagues developed an AI-based tool called CellCNN to identify rare cell populations in flow cytometry data, which could have significant implications in the diagnosis and monitoring of various diseases [ 69 ].…”
Section: Current Applications Of Ai In Hematologic Cytologymentioning
confidence: 99%
“…Recent studies explored the use of AI in other areas of flow cytometric analysis beyond disease classification. Studies indicated that an AI-based method for automated gating of cell populations in flow cytometry data achieves high accuracy and consistency across different datasets [ 68 ]. In addition, Arvaniti and colleagues developed an AI-based tool called CellCNN to identify rare cell populations in flow cytometry data, which could have significant implications in the diagnosis and monitoring of various diseases [ 69 ].…”
Section: Current Applications Of Ai In Hematologic Cytologymentioning
confidence: 99%
“…Addressing this problem requires the simultaneous optimization of cell population identification (biomarkers) and sample-level classification (diagnosis). In previous work [21], we showed that the simultaneous optimization can be achieved for diagnosis of chronic lymphocytic leukemia (CLL), by adapting gradient descent optimization for identifying a global optimal gate to maximize classification accuracy. In this paper, we hypothesize that a density-based discriminative point set model using backpropagation can address the simultaneous optimization, without requiring initial gating.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing this problem requires the simultaneous optimization of cell population identification (biomarkers) and sample-level classification (diagnosis). In previous work ( Ji et al 2020 ), we showed that the simultaneous optimization can be achieved for diagnosis of chronic lymphocytic leukemia (CLL), by adapting gradient descent optimization for identifying a global optimal gate to maximize classification accuracy. In this article, we hypothesize that a density-based discriminative point set model using backpropagation can address the simultaneous optimization, without requiring initial gating.…”
Section: Introductionmentioning
confidence: 99%